KAJIAN TEOLOGIS TENTANG PENDIDIKAN ANAK USIA DINI DALAM ALKITAB - Steven Tubagus (Institut Agama Kristen Negeri Kupang, 2023)
The background of the problem is the lack of enthusiasm in early childhood and the lack of parental ability in accompanying early childhood into bad habits and also the lack of God's word to early childhood so that mistakes occur in bad behavior, for example shouting, cursing, like hitting, not wanting to worship, and likes to fight parents. Theological Study of Early Childhood Education in the Bible. The purpose of this paper is to describe the Theological Study of Early Childhood Education in the Bible. By analyzing the text in accordance with the principles of exegesis, to get the meaning and results contained in the context of the Theological Study of Early Childhood Education in the Bible The results of the descriptive analysis of the Theological Study of Early Childhood Education in the Bible are first, early childhood recognizes the Torah and celebrations holidays through parents. Second, understand religion, such as religious values, the introduction of the Lord Jesus, the procedures for worship and prayer, and the implementation of religion in life. Third, early childhood can pray, memorize, sing, and testify about Jesus. Description of Theological Study of Early Childhood Education in the Bible consists of: First, the Old Testament. Spiritual education and formation in the Old Testament world usually took place at home, in the context of worship and at court. Of course there is no education that is ready for everyone as in the present era. In general, the family context is the most central place for education and coaching. Second, the New Testament. The role of parents in building perseverance in early childhood, fathers in Christian families are expected to start introducing perseverance as early as possible since children can communicate or respond when spoken to or taught something, for example, perseverance in praying is taught to early childhood, namely praying before going to bed, wake up, and every time you want to eat. Third, Bible Analysis. Moses warned the Israelites to teach the word of God to children from an early age from every generation. How important is God's word to be an inheritance for early childhood according to the Torah, even early childhood must understand the confession of faith. God's church must do the same, which is to teach children from an early age as a new generation. The gospel is the good news of knowing the person and work of redemption of the Lord Jesus that must be taught to children from an early age from every generation.